Implementasi Model Problem Based Learning (PBL) Untuk Meningkatkan Pemahaman Konsep Matematis - Aprian, Reinaldi; Aulia, Hilyatul; Fauziah, Nazwa Rifa; Lestari, Amanah Puji; Budiyanto, Aris (Universitas Pekalongan, 2025)
Understanding mathematical concepts is an important foundation for students in learning further material. However, many students still have difficulty with the concept of integers.This study aims to improve students' mathematical conceptual understanding of integers through the application of the Problem-Based Learning (PBL) model. The research was conducted at MTs Nurul Huda Depok with 27 seventh-grade students as participants. The method employed was Classroom Action Research (CAR), which consisted of two cycles, each comprising three meetings. The research instruments included a conceptual understanding test, observation sheets for teacher and student activities, interviews, and field notes. The results showed an improvement in students' mathematical conceptual understanding after the implementation of the PBL model. Initially, the average student score was 61%, indicating a low level of mastery. After the first cycle, the average score increased, although it had not yet met the success indicator. In the second cycle, however, the average score rose significantly, achieving over 80% classical mastery in line with the established success criteria. Thus, it can be concluded that the implementation of the Problem-Based Learning (PBL) model is effective in enhancing students' mathematical conceptual understanding of integers in the seventh grade at MTs Nurul Huda Depok Keywords: Classroom action research, conceptual understanding, problem based learning